Unraveling the complexity of land use change and path dependency in agri-environmental schemes for small farmers: A serious game approach - Yair Asael Alpuche Álvarez; Martin Rudbeck Jepsen; Daniel Müller; Laura Vang Rasmussen; Sun Zhanli (Land Use Policy, 2024)
This study investigates how Maya farmers in Mexico respond to agri-environmental subsidies aimed at promoting sustainable land use decisions. We do so through a serious games approach, using a tailor-designed board game to identify the land use behaviors of Maya farmers. The game simulated three different subsidy programs promoting mechanized agriculture, forest conservation, and agroforestry. We find that farmers tend to clear forested areas in response to agroforestry subsidies. Also, we observe that land use decisions are path-dependent, with farmers adhering to traditional and mechanized agriculture and hesitant to engage in conservation and agroforestry. These findings highlight the potential of serious games as a tool to improve understandings of how farmers make land use decisions and the resulting land use change patterns. Specifically, our findings show that serious games are well suited to understand how path dependency in decision-making can influence the effect of subsidies – and whether subsidies thereby achieve the intended goals, such as reduced deforestation.
Keywords: 630; land use complexity; land use decisions; Maya farmers; political drivers; serious games